Espaços públicos urbanos & relações intergeracionais: Affordances de suporte a jovens e idosos no centro histórico de Pelotas. - Libardoni, Thaís Debli (2018)
Urban sociability is especially significant for vulnerable social groups such as young and old people, but public spaces can generate segregation by lack of attractiveness or support for specific users. Age segregation and ageism can be softened by intergenerational relations. In this sense, studies have highlighted similarities of social, physical and psychological needs and environmental perceptions among young and old people. However, research on intergenerational relations is still scarce, especially studies that consider the perception and behavior of these two age groups. Based on the Theory of Affordances, this research aims to contribute with recommendations for the design of public spaces that opportunize the intergenerational coexistence of the two age groups.The specific aims are: (i) to investigate the position of young and old people on intergenerational relations; (ii) find out if the available uses and social spaces correspond to their contemporary needs; (iii) identify their places of appropriation and rejection and the main reasons; (iv) to carry out a comparative age study of perceptions; and (v) analyze data through affordances and behaviour resulting in spatial attributes, settings and qualities.Through an ecological perspective, the case study was carried out in Pelotas, initially in the typologies: urban park, largo of the public market, central square and pedestrian street. Bibliographical and documentary research, physical survey, behavioral maps and questionnaires were carried out. The finding of copresence and interaction between the young people and the elderly and the evidence that constructed stereotypes are not significant, refute a direct age conflict. Similar habitus differentiate them from other age groups and produce similar appropriations in the form of age microterritories with different meanings. The study recognizes the microterritories within an intergenerational context as fomenters of urban sociability. The findings corroborate the search for the conflict resolution inherent to each age group, resulting in the longing for similar affordances, but in different ways. This complexity results in recommendations for: Movement, Tranquility, Shading, Safety, Agradability, Activities, Variety, Meeting Places, Habit, Proximity and Options for Sitting.